A Case Report of Neuronal Intranuclear Inclusion Disease Presenting With Recurrent Migraine-Like Attacks and Cerebral Edema: A Mimicker of MELAS - Xie, Fei; Hu, Xingyue; Liu, Peng; Zhang, Dan (Frontiers in Neurology, 2022)
Background: Neuronal intranuclear inclusion disease (NIID) is a progressive neurodegenerative disease caused by the GGC repeats in the 5’-untranslated region (5’UTR) of NOTCH2NLC. NIID exhibits a wide range of clinical manifestations. However, patients presenting with recurrent migraine-like attacks and cerebral edema have only rarely been reported. Case Presentation: A Chinese female suffered probable migraines with aura for 10 years. At age of 51, aggravating migraine-like attacks co-occurred with a sudden encephalopathy-like episode. Brain MRI showed right cerebral edema and cortical enhancement. Serum lactic acid level was elevated at rest and significantly increased after a simplified serum lactic acid exercise test. The initial diagnosis was MELAS, while NIID was suspected after faint DWI high-intensity signals in the corticomedullary junction was retrospectively recognized. Mitochondrial genome sequencing and gene panel analysis of nuclear genes related to mitochondrial diseases failed to find any causative variants. Repeat-primed PCR and fluorescence amplicon length PCR of NOTCH2NLC gene identified an abnormal expansion of 118 GGC repeats in the 5’UTR of NOTCH2NLC gene. Conclusion: NIID should be taken into account for differential diagnosis of migraines and MELAS-like episodes. Besides the corticomedullary hyperintensity on DWI, cortical enhancement in contrast-enhanced brain MRI may also be a brain image marker for the differential diagnosis between MELAS and NIID with MELAS-like episodes.